ANALISIS TATA LETAK PENYIMPANAN PRODUK JADI MENGGUNAKAN METODE SHARED STORAGE PADA GUDANG PRODUK JADI DI PT SINAR SOSRO KPB PALEMBANG - Meilizar Meilizar; Widya Suci Wahyuni (Politeknik ATI Padang, 2018)
PT Sinar Sosro KPB Palembang is a manufacturing company that produces several tea-based beverage products packed with glass bottles and plastic bottles. The problems that occur in PT Sinar Sosro Palembang KPB are irregularities in the preparation of products, this will hamper the process of importing goods to the warehouse and taking the items to be distributed. This study aims to propose improvements to the warehouse layout. The method used in this study is a shared storage method in which products that have the most frequency of delivery and that are often in and out are brought close to the entrance to minimize the distance of material handling transfer. The results obtained based on the shared storage approach is to classify products based on the volume of content and type of product so as to facilitate the process of product search and move the location of product storage based on monthly frequency requests, products with high demand are placed close to the exit so that the distance of product retrieval is more close to the loading.